32nd AIAA Applied Aerodynamics Conference 2014
DOI: 10.2514/6.2014-2441
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of a Flexible Wing with a Variable Camber Continuous Trailing Edge Flap Design

Abstract: This paper presents experimental results of a flexible wing wind tunnel model with a variable camber continuous trailing edge flap (VCCTEF) design for drag minimization, tested at the University of Washington Aeronautical Laboratory (UWAL). The wind tunnel test was designed to explore the relative merit of the VCCTEF concept for improved cruise efficiency through the use of low-cost aeroelastic model test techniques. The flexible wing model is a 10%-scaled model of a typical transport wing and is constructed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 5 publications
1
31
0
1
Order By: Relevance
“…6 The wind tunnel test results showed a drag reduction of up to 6.31% and an improvement in lift-to-drag ratio (L/D) of up to 4.85% for the configurations tested. 7 A previous study constructed an aeroelastic model based on a computational fluid dynamic (CFD) Euler code called CART3D that showed agreement with wind tunnel results. 8 This paper outlines the development and validation of a static aeroelasticity model based upon the sub-scale model of the wing with VCCTEF tested at UWAL.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…6 The wind tunnel test results showed a drag reduction of up to 6.31% and an improvement in lift-to-drag ratio (L/D) of up to 4.85% for the configurations tested. 7 A previous study constructed an aeroelastic model based on a computational fluid dynamic (CFD) Euler code called CART3D that showed agreement with wind tunnel results. 8 This paper outlines the development and validation of a static aeroelasticity model based upon the sub-scale model of the wing with VCCTEF tested at UWAL.…”
Section: Introductionmentioning
confidence: 55%
“…Collated information summarizing the wind tunnel test results are found in references. 6,7 Figure 6 is a photo of the model being tested in the UWAL wind tunnel. …”
Section: Wind Tunnel Model Of Flexible Wingmentioning
confidence: 99%
“…The nominal dynamic pressure is 20 psf. The full report of the wind tunnel test data analysis is published by Nguyen et al 13 For summary, only test data for FLAP0 configuration is shown. The lift curve and drag polar for the baseline FLAP0 configuration are plotted in Figs.…”
Section: Summary Of Wind Tunnel Experimental Datamentioning
confidence: 98%
“…13 The aeroelastic deflection correction method yields the highest estimated rigid-wing lift coefficient. Since there are some differences in the three estimated rigid wing lift coefficients, an average rigid wing lift coefficient is computed and is shown in Fig.…”
Section: Summary Of Wind Tunnel Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation